The visual identity of Indonesian post-structuralism in @visual.jalanan’s Instagram street art - Kristiyono, Jokhanan; Febriyanti, Syafrida N.; Ida, Racmah (Jurnal Studi Komunikasi, 2024)
This study examines how post-structuralist visual identities and counter-hegemonic practices are expressed through digital street art on the Instagram account specifically onn @visual.jalanan account. Using a qualitative content analysis, this research focuses on posts made between January to May 2024, coding visual and textual elements to identify themes of hybridity, fragmentation, and resistance. This study selected 127 posts based on relevance to socio-political discourse and public engagement metrics such as likes and comments. The findings reveal that Instagram serves as a platform for cultural expression and social critique, enabling artists to bypass traditional gatekeepers. The artworks analysed in this study challenge dominant narratives related to nepotism, political propaganda, corruption, and cultural homogeneity. These artworks foster fluid identities and critical dialogue through visual satire and audience interaction, exemplifying post-structuralist principles. This research highlights Instagram’s role as a counter-hegemonic medium that contests mainstream narratives by amplifying marginalised voices. The study contributes to the scholarship on digital media art and visual identity by demonstrating how digital platforms enable innovative artistic expression and resistance to socio-political structures. Future research should explore the evolving role of digital platforms in sustaining counter-hegemonic movements and engaging with political advocacy in Indonesia.